Coconut-based bacterial cellulose carbon nanofibers. (23rd February 2017) - Zhao, Zhiming; Hua, Yingjie; You, Chenghang; Li, Yi; Liu, Huan; Huang, Huihao; Wu, Xiaofang; Wang, Yizhen; Wang, Chongtai
Abstract : A series of porous carbon nanofibres, with network-like structures and high surface area, were prepared using low-cost renewable bacterial cellulose, fabricated from the raw materials of coconut. The performances of these coconut-based bacterial cellulose carbon nanofibres (BCCNFs) strongly rely on their porous network-like graphitised structure. The carbonisation temperatures affect both the graphitic degree of BCCNFs and the uniformity of their porous structure. The specific capacitance of BCCNFs at 900 °C drops off due to the decrease in the uniformity of their porous structure. The prepared BCCNFs materials exhibited high electrochemical energy storage performance (with its specific capacitance in 6 M KOH solution being 289 F g −1 ) and cycling excellent stability (after 5000 charge–discharge cycles, the material still maintained more than 80% of its initial capacitance), making them potential for the practical application of supercapacitors.